Therapeutic ultrasound transducer technology and monitoring techniques: a review with clinical examples - Maxime Lafond; Allison Payne; Cyril Lafon (International Journal of Hyperthermia, 2024)
The exponential growth of therapeutic ultrasound applications demonstrates the power of the technology to leverage the combinations of transducer technology and treatment monitoring techniques to effectively control the preferred bioeffect to elicit the desired clinical effect.Objective: This review provides an overview of the most commonly used bioeffects in therapeutic ultrasound and describes existing transducer technologies and monitoring techniques to ensure treatment safety and efficacy.Methods and materials: Literature reviews were conducted to identify key choices that essential in terms of transducer design, treatment parameters and procedure monitoring for therapeutic ultrasound applications. Effective combinations of these options are illustrated through descriptions of several clinical indications, including uterine fibroids, prostate disease, liver cancer, and brain cancer, that have been successful in leveraging therapeutic ultrasound to provide effective patient treatments.Results: Despite technological constraints, there are multiple ways to achieve a desired bioeffect with therapeutic ultrasound in a target tissue. Visualizations of the interplay of monitoring modality, bioeffect, and applied acoustic parameters are presented that demonstrate the interconnectedness of the field of therapeutic ultrasound. While the clinical indications explored in this review are at different points in the clinical evaluation path, based on the ever expanding research being conducted in preclinical realms, it is clear that additional clinical applications of therapeutic ultrasound that utilize a myriad of bioeffects will continue to grow and improve in the coming years.Conclusions: Therapeutic ultrasound will continue to improve in the next decades as the combination of transducer technology and treatment monitoring techniques will continue to evolve and be translated in clinical settings, leading to more personalized and efficient therapeutic ultrasound mediated therapies.